Prevention and Treatment of Fungal Skin Infections Using Cationic Polymeric Films - Fritz Ka-Ho Ho; Albert Bolhuis; M. Begoña Delgado-Charro (Pharmaceutics, 2021)
Dermatophytosis is a fungal infection of skin, nails and hair. Treatments can be long and infections are often recurrent, and novel treatments are desirable. Here we tested the use of polymeric films that can be sprayed on the skin for the prevention and treatment of dermatophytosis. The two polymers selected were ABIL T Quat 60 and Eudragit E100, which were tested ex vivo using a porcine skin model, and in vitro using microbiological and microscopy techniques. Acceptability of the polymeric films was tested on the skin of healthy volunteers. The results showed that ABIL and Eudragit films prevented and treated fungal skin infections. Whilst polymer films may provide a physical barrier that prevents fungal colonization, it was shown that both polymers are active antifungals ex vivo and in vitro and have intrinsic antifungal activity. For ABIL, we also established that this polymer binds essential nutrients such as metal ions and sugars, thereby restricting the growth of fungi. When applied to healthy subjects’ skin, the polymeric films neither modified the skin color nor increased trans-epidermal water loss, suggesting a low potential for skin irritation, and the approach was generally found to be acceptable for use by the volunteers. In conclusion, we developed a novel strategy for the potential prevention and treatment of dermatophytosis.